Natural Organic Matter Removal and Fouling in a Low Pressure Hybrid Membrane Systems. (8th January 2014) - Uyak, Vedat; Akdagli, Muge; Cakmakci, Mehmet; Koyuncu, Ismail
Abstract : The objective of this study was to investigate powdered activated carbon (PAC) contribution to natural organic matter (NOM) removal by a submerged MF and UF hybrid systems. It was found that filtration of surface waters by a bare MF and UF membranes removed negligible TOC; by contrast, significant amounts of TOC were removed when daily added PAC particles were predeposited on the membrane surfaces. These results support the assumption that the membranes surface properties and PAC layer structure might have considerably influential factor on NOM removal. Moreover, it was concluded that the dominant removal mechanism of hybrid membrane system is adsorption of NOM within PAC layer rather than size exclusion of NOM by both of membrane pores. Transmembrane pressure (TMP) increases with PAC membrane systems support the view that PAC adsorption pretreatment will not prevent the development of membrane pressure; on the contrary, PAC particles themselves caused membrane fouling by blocking the entrance of pores of MF and UF membranes. Although all three source waters have similar HPI content, it appears that the PAC interaction with the entrance of membrane pores was responsible for offsetting the NOM fractional effects on membrane fouling for these source waters.